2022
DOI: 10.1039/d2dt00237j
|View full text |Cite
|
Sign up to set email alerts
|

Exchange-driven slow relaxation of magnetization in NiII2LnIII2 (LnIII = Y, Gd, Tb and Dy) butterfly complexes: experimental and theoretical studies

Abstract: The tetranuclear NiII2LnIII2 complexes, [{L′2{Ni(MeOH)(μ-OAc)}2(μ3-MeO)2Ln2}; LnIII = YIII (1), GdIII (2), TbIII (3), DyIII (4)] were prepared using a Schiff base ligand, H3L [H3L = 3-((2-hydroxy-3-methoxybenzylidene)amino)-2-(2-hydroxy-3-methoxyphenyl)-2,3-dihydroquinazolin-4(1H)-one, whereas {L′}3- is the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
(115 reference statements)
0
13
0
Order By: Relevance
“…Therefore, suppressing the QTM effect is still a current challenge for chemists that needs to be explored. The previous experimental and theoretical studies have confirmed that introducing strong spin–spin exchange coupling between metal ions and defining high-crystal field symmetry around individual lanthanide ions are two main strategies to suppress the QTM effect. In view of the above considerations, various 3d-4f heterometallic complexes with strong magnetic interactions existing in the heterometallic clusters are constructed, in which the metal ions are bridged by monatomic oxygen. Meanwhile, a more efficient exchange coupling can also be obtained through optimizing the crystal field of Dy III ions by selecting transition metal ions reasonably . As expected, the studies of butterfly type [Co II 2 Dy III 2 ] by Powell and Song suggest the magnetic coupling between 3d and 4f ions can significantly reduce the QTM effect. , However, there are only a few examples reported so far.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, suppressing the QTM effect is still a current challenge for chemists that needs to be explored. The previous experimental and theoretical studies have confirmed that introducing strong spin–spin exchange coupling between metal ions and defining high-crystal field symmetry around individual lanthanide ions are two main strategies to suppress the QTM effect. In view of the above considerations, various 3d-4f heterometallic complexes with strong magnetic interactions existing in the heterometallic clusters are constructed, in which the metal ions are bridged by monatomic oxygen. Meanwhile, a more efficient exchange coupling can also be obtained through optimizing the crystal field of Dy III ions by selecting transition metal ions reasonably . As expected, the studies of butterfly type [Co II 2 Dy III 2 ] by Powell and Song suggest the magnetic coupling between 3d and 4f ions can significantly reduce the QTM effect. , However, there are only a few examples reported so far.…”
Section: Introductionmentioning
confidence: 98%
“…30,31 Apart from that, the Ni II centre often exhibits ferromagnetic exchange coupling with 4f metal ions. [32][33][34][35][36][37] Hence, the new family of SMMs possessing large effective energy barriers for the reversal of magnetization (U eff ), and hence higher blocking temperatures (T B ), can be constructed by putting highly anisotropic trivalent 4f and bivalent Ni ions in close proximity. The higher coordination requirement around the Ln III ions following ligand chelation is achieved by inorganic anions like NO 3 − , RCO 2 − etc.…”
Section: Introductionmentioning
confidence: 99%
“…55 In this context, computational tools in the density functional theory (DFT) and post-Hartree-Fock-based CASSCF/CASPT2 methods have played a profound role in correlating the electronic structure and magnetic anisotropy of lanthanide-based molecular magnets. 25,27,35,38,45,52,[56][57][58][59][60][61] Several attempts have been made to investigate the covalency effects by substituting ligands with formal charges or using more complex effective charge models to understand how covalency influences the magnetic anisotropy of Ln(III) ions. 51,52,[61][62][63][64] In one of the seminal works, Ungur et al have rigorously discussed ab initio crystal field and atomic point charge crystal field model approaches to study the crystal field effects in lanthanide complexes.…”
Section: Introductionmentioning
confidence: 99%